2010
DOI: 10.1016/j.jacc.2010.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epicardial Fat on Electroanatomical Mapping and Epicardial Catheter Ablation

Abstract: Cardiac CT identifies epicardial fat that can mimic scar tissue during epicardial EA voltage mapping, which is important during epicardial mapping and ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 9 publications
2
79
0
1
Order By: Relevance
“…20,21 Indeed, the 3 ECG features found to be more prevalent in successful versus unsuccessful cases (ie, Q-wave ratio aVL/aVR >1.85, R/S ratio in V1>2, and lack of q wave in V1) and reflect a more lateral site of origin of the VAs (distant from the midline and the apex of the LVS triangle). Accordingly, more patients in the successful group had a QS pattern in lead I, which again points to a more lateral (and epicardial) origin of the VAs.…”
Section: Ecg Features Associated With Successful Epicardial Ablationmentioning
confidence: 99%
“…20,21 Indeed, the 3 ECG features found to be more prevalent in successful versus unsuccessful cases (ie, Q-wave ratio aVL/aVR >1.85, R/S ratio in V1>2, and lack of q wave in V1) and reflect a more lateral site of origin of the VAs (distant from the midline and the apex of the LVS triangle). Accordingly, more patients in the successful group had a QS pattern in lead I, which again points to a more lateral (and epicardial) origin of the VAs.…”
Section: Ecg Features Associated With Successful Epicardial Ablationmentioning
confidence: 99%
“…To minimize the effect of epicardial fat on low-voltage area measurements, the anterior interventricular sulcus and the AV grove (defined as the first centimeter from mitral and tricuspid annuli) were not considered for segmentation when contouring epicardial low-voltage areas. 23 The distribution of LAVA sites with respect to this substrate was analyzed, and the density of LAVA sites per centimeter square of substrate was assessed and compared between the RV and the LV. To avoid a double counting of LAVAs, 2 sites were considered different if the distance between both sites was >3 mm.…”
Section: Post Hoc Analysismentioning
confidence: 99%
“…This underscores the importance of identifying both structures and understanding their anatomic relationship with coronary arteries before and during epicardial mapping and ablation. 13 Currently there is no accepted strategy for this purpose. Additionally, it has been suggested that ablation from epicardial veins would be feasible, 12,14 but our results indicate that ablating in close proximity to the epicardial coronary arteries without venous structure interposed could potentially lead to more severe vessel injuries.…”
Section: Present Findingsmentioning
confidence: 99%